In vitro study of polydopamine nanoparticles as protective antioxidant agents in fibroblasts derived from ARSACS patients. (30th May 2022) - Battaglini, Matteo; Carmignani, Alessio; Martinelli, Chiara; Colica, Jamila; Marino, Attilio; Doccini, Stefano; Mollo, Valentina; Santoro, Francesca; Bartolucci, Martina; Petretto, Andrea; Santorelli, Filippo Maria; Ciofani, Gianni
Abstract : PDNPs elicit an antioxidant effect on healthy and ARSACS-derived fibroblasts, thus reducing ROS levels, ROS-induced apoptosis/necrosis, and ROS-induced mitochondrial impairments, and enhancing protein expression. Abstract : Reactive oxygen species (ROS) are active molecules involved in several biological functions. When the production of ROS is not counterbalanced by the action of protective antioxidant mechanisms present in living organisms, a condition of oxidative stress can arise with consequent damage to biological structures. The brain is one of the main ROS-generating organs in the human body, with the consequence that most of the neurological disorders are associated with an overproduction of ROS. Autosomal recessive spastic ataxia of Charlevoix-Saguenay (ARSACS) is a neurodegenerative disease associated with mutations in the sacsin gene ( SACS ). At cellular level, ARSACS is characterized by mitochondrial impairments, a reduction in bioenergetic processes, and by both an over-production of and an over-sensitivity to ROS. Several antioxidant molecules have been proposed as a potential treatment for ARSACS, such as idebenone and resveratrol. Polydopamine nanoparticles (PDNPs) gained significant attention in recent years owing to their peculiar physical/chemical properties, and especially because of their antioxidant activity. PDNPs have shown a great ROS scavenging capacity that, combined with their completely organic nature that grants them the ability to be degraded and excreted by living organisms, make them a promising candidate in the treatment of oxidative stress-related disorders. In this work, we assessed the effect of PDNPs on human fibroblasts derived from ARSACS patients in terms of antioxidant properties and protein expression. PDNP interaction with fibroblasts was analyzed in terms of biocompatibility, internalization and uptake pathway, reduction of ROS levels, prevention of ROS-induced apoptosis/necrosis, and protective action upon ROS-induced mitochondrial dysfunctions. Moreover, a complete proteomic analysis was performed. Altogether, our data showed that PDNPs can partially counteract ROS-induced damages in ARSACS patient-derived fibroblasts, making them a potential therapeutic candidate to treat – or at least to ameliorate – the condition of oxidative stress associated with ARSACS.